EDUCATIONAL FACTORS PROVIDING PROFESSIONAL MOBILITY OF WORKERS - Andrii Shegda (Izdevnieciba "Baltija Publishing", 2016)
The essence of professional mobility has been defined in the article. The role of education in the system of causes of occupational mobility has been presented. Current trends of the professional mobility on the national labor market have been analyzed.